Prarancangan Pabrik Dibutyl Phthalate dari Phthalic Anhydride dan N-Butanol Kapasitas 21.000 Ton/Tahun - Kirana, Therisia Widi; , Dr. Achmad M. Fuadi, M.T; , Kusmiyati, S.T, M.T, Ph.D (2015)
The background of the establishment of the factory dibutyl phthalate is to reduce dependence on imported materials originating from foreign industry. In addition, as providers of auxiliary materials for the polymer industry and other industries that require dibutyl phthalate. The existence of the establishment of the plant is also expected to increase the income of the Indonesian state. This plant is designed with a production capacity of 21.000 tons / year and will be established in Gresik, East Java. Dibutyl phthalate is one kind of plasticizer (plastic additional material to enhance the durability, transparency properties, and the properties of plasticity) where the synthesis of dibutyl phthalate occurs through esterification reaction between phthalic anhydride and n-butanol. The process requires sulfuric acid catalyst to accelerate the reaction because the reaction takes place in two stages. Esterification reaction occurs in stirred tank flow reactor (RATB) with 140C operating temperature and pressure of 2 atm. Wherein the reaction is exothermic so that the necessary cooling medium such as water to keep the reaction temperature constant. Product out of the reactor is fed to a separator to separate the liquid phase and vapor. The vapor phase will be fed to the distillation tower-01. Meanwhile, the acidic aqueous phase will be fed to the reaction neutralizer and neutralization with NaOH. After that, the mixture is fed into the decanter. In the decanter separation of components based on specific gravity. The top layer in the form of the product will go to the distillation tower 02 to the purification process and the product will be towards the lower layers waste treatment unit. Utility unit is a unit which supports all the needs of the process at the factory. Utilities are required factory dibutyl phthalate include the provision of water as much as 7.100 kg / h obtained from the Brantas river water, steam demand as much as 10.100 kg / h obtained from the boiler. Needs a total of 100 kW of electricity obtained from the PLN and generator sets with a capacity of 350 kW. Fuel used for boilers and generators are diesel fuel requirements by 940 L / h. The factory dibutyl phthalate Limited Liability Company (PT) with the number of employees 170 people and operated for 330 days in one year. Working capital at this plant Rp. 59.123.068.847,11 per year and fixed capital of Rp. 326.709.619.077,99 per year. From the economic analysis of the plant, the plant has a pretax profit of Rp. 91.808.755.987,07 per year and profit after tax of Rp. 64.266.129.190,95 per year. Percent return on investment (ROI) before tax of 28,10% and after tax of 19,67%. Pay out time (POT) before tax of 2,62 years and 3,37 years after tax. Break even point (BEP) of 50,5%, shut down point (SDP) amounted to 27,88%, IRR based on discounted cash flow (DCF) of 41,3%. Based on the above analysis, it can be concluded that the plant dibutyl phthalate can benefit so it is worth to be established.